Assessing Fraud Deterrence In Private Health Clinics: Policy Implications From West Java - Koenta Adji Koerniawan; Galuh Tresna Murti; Rr Sri Saraswati; Hilda Hilda (Jurnal Reviu Akuntansi dan Keuangan, 2024)
Purpose: Investigate whether the application of the Fraud Deterrence Propeller (FDP) protocol to assess the entity's maturity level in deterring fraud in privately owned health clinics can be applied, and investigate how the West Java provincial health service regulations relate to preventing fraud in health clinic providers. Methodology/approach: Using a qualitative case study approach with post-positivism philosophy. In-depth interviews with 10 key informants, as well as field observations and literature reviews, were conducted. Data is processed with QDA Miner. Findings: The FDP protocol can be applied to health clinics in Bandung to assess an entity's fraud deterrence maturity level. The dimensions of the FDP concept are used in fraud deterrence policies in the health environment of West Java Province, but are mandatory only in government-owned clinics, and do not apply to private clinics. Practical implications: Private health clinic providers understand the urgency of implementing the FDP protocol to assess fraud prevention maturity. The West Java provincial health service is considering expanding fraud deterrence regulations for private health clinics, especially the implementation of an internal control system and Fraud Control Plan (FCP) and Whistle-Blowing System. Originality/value: The novelty of this research is the use of the Fraud Deterrence Propeller (FDP) protocol in private health clinic providers.